2011
DOI: 10.1038/cmi.2010.77
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulation in the era of the metagenome

Abstract: Microbes are increasingly being implicated in autoimmune disease. This calls for a re-evaluation of how these chronic inflammatory illnesses are routinely treated. The standard of care for autoimmune disease remains the use of medications that slow the immune response, while treatments aimed at eradicating microbes seek the exact opposite-stimulation of the innate immune response. Immunostimulation is complicated by a cascade of sequelae, including exacerbated inflammation, which occurs in response to microbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 132 publications
0
14
0
Order By: Relevance
“…Furthermore, the same mice prophylactically treated with the ODN resisted MRSA infection. Treatments aimed at restoring the host's immune function have been shown to be effective for preventing the onset of infections in immunocompromised hosts; 24 , 25 , 26 , 27 , 28 , 29 however, the control of MRSA infection using immunologically acting substances remains limited. In our studies, the growth of MRSA was shown to be minimal in the blood and other organs of 25% TBSA burn mice therapeutically treated with the ODN.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the same mice prophylactically treated with the ODN resisted MRSA infection. Treatments aimed at restoring the host's immune function have been shown to be effective for preventing the onset of infections in immunocompromised hosts; 24 , 25 , 26 , 27 , 28 , 29 however, the control of MRSA infection using immunologically acting substances remains limited. In our studies, the growth of MRSA was shown to be minimal in the blood and other organs of 25% TBSA burn mice therapeutically treated with the ODN.…”
Section: Discussionmentioning
confidence: 99%
“…(299309)]; they may also be detected ultramicroscopically [e.g., Ref. (139141, 190, 267, 300, 310)] or by flow cytometry (311), and dormant blood and tissue microbes probably underpin a great many chronic, inflammatory diseases normally considered to lack a microbial component (139141, 144147, 190, 267, 268, 302, 312–321). Multiple arguments serve to exclude “contaminants” as the source of the bacterial DNA (141): (1) there are significant differences between the blood microbiomes of individuals harboring disease states and nominally healthy controls, despite the fact that samples are treated identically; (2) the morphological type of organism (e.g., coccus vs. bacillus) seems to be characteristic of particular diseases; (3) in many cases, relevant organisms lurk intracellularly, which is hard to explain by contamination; (4) there are just too many diseases where bacteria have been found to play a role in the pathogenesis, that all of them may be caused by contamination; (5) the actual numbers of cells involved seem far too great to be explicable by contamination; given that blood contains ~5 × 10 9 erythrocytes mL −1 , if there was just one bacterial cell per 50,000 erythrocytes this will equate to 10 5 bacteria mL −1 .…”
Section: Prevalence Of Dormant Persistent or Latent Bacteria In Infmentioning
confidence: 99%
“…[291301]); they may also be detected ultramicroscopically (e.g. [132134; 183; 259; 292; 302]) or by flow cytometry [303], and dormant blood and tissue microbes probably underpin a great many chronic, inflammatory diseases normally considered to lack a microbial component [132134; 137140; 183; 259; 260; 294; 304–313]. Multiple arguments serve to exclude ‘contaminants’ as the source of the bacterial DNA [134]: 1.…”
Section: Introductionmentioning
confidence: 99%